Imperfect competition, general equilibrium and unemployment - Gersbach, Hans; Schniewind, Achim (CESifo working papers, 1999)
We analyze whether different learning abilities of firms with respect to general equilibrium effects lead to different levels of unemployment. We consider a general equilibrium model where firms in one sector compete à la Cournot and a real wage rigidity leads to unemployment. If firms consider only partial equilibrium effects when choosing quantities, the observation of general equilibrium feedback effects will lead to repeated quantity adjustments until a steady state is reached. When labor is im mobile across industries, unempolyment in the steady state is lower than when all general equilibrium effects are incorporated at once. The opposite result is true if labor is mobile.
Keywords: Graue Literatur; Arbeitslosigkeit; Gleichgewichtstheorie; Unvollständige Konkurrenz